1994
DOI: 10.1161/01.hyp.24.1.106
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive effect of pioglitazone is not invariably associated with increased insulin sensitivity.

Abstract: Hypertension is often associated with insulin resistance, and several chemically diverse agents that increase insulin sensitivity attenuate the development of experimental hypertension. We undertook the present study to determine whether attenuation of hypertension by pioglitazone, a thiazolidinedione derivative that increases insulin sensitivity without increasing insulin secretion, is specifically related to its effect on insulin-mediated glucose uptake. Pioglitazone administered daily by oral gavage (20 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
3

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 22 publications
2
37
3
Order By: Relevance
“…Therefore, it is suggested that pioglitazone exerts its antihypertensive effect by improving insulin sensitivity and also by another mechanism. In recent studies, pioglitazone showed a direct effect on vascular smooth muscle cells to inhibit calcium ion influx, resulting in the inhibition of blood vessel constriction and vascular cell growth and decreasing the blood pressure (27)(28)(29). In this study, however, the improvement of insulin resist ance rather than the direct effect of pioglitazone on arterial cells seems to contribute much to the blood pressure reduction.…”
Section: Discussioncontrasting
confidence: 52%
“…Therefore, it is suggested that pioglitazone exerts its antihypertensive effect by improving insulin sensitivity and also by another mechanism. In recent studies, pioglitazone showed a direct effect on vascular smooth muscle cells to inhibit calcium ion influx, resulting in the inhibition of blood vessel constriction and vascular cell growth and decreasing the blood pressure (27)(28)(29). In this study, however, the improvement of insulin resist ance rather than the direct effect of pioglitazone on arterial cells seems to contribute much to the blood pressure reduction.…”
Section: Discussioncontrasting
confidence: 52%
“…[3][4][5][6]23,24 Similarly, others have demonstrated that the acute change in blood pressure and vascular function in rats caused by angiotensin II infusion (osmotic minipumps) or endothelin (deoxycorticosterone acetate [DOCA] salt) can be prevented by simultaneous treatment with TZDs. 25,26 This is the first study, to our knowledge, demonstrating that treatment with rosiglitazone can ameliorate lifelong renin-angiotensin-induced hypertension and extends the beneficial blood pressure effects of TZDs to a murine model of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…This potent effect of troglitazone on All-induced signalling might contribute to the observed in vivo effects of troglitazone to prevent neointimal hyperplasia in the injured vessel and to lower blood pressure in some animal models of hypertension. Tro and related thiazolidinediones have been shown to attenuate hypertension an a variety of animal models [15,16]. As insulin sensitizers these agents could lower blood pressure indirectly by improving insulin resistance [17].…”
Section: Referencesmentioning
confidence: 99%